A study on sexual functioning and depression in Iranian women following cesarean hysterectomy due to placental abnormality after 3–6 months. Issue 6 (3rd July 2021) - Ghotbizadeh, Fahimeh; Hantoushzadeh, Sedigheh; Borna, Sedigheh; Khazardoost, Soghra; Panahi, Zahra; Ghamari, Azin; Dehghani, Atefeh; Raisi, Firoozeh
ABSTRACT: This study aims to investigate the prevalence of depression and impaired sexual function following the hysterectomy in Iran. This study was performed as a retrospective cohort study, from August 2017 to August 2018. Fifty-two patients with a cesarean hysterectomy and 52 with cesarean section were considered as the cases and controls, respectively. Depression and sexual function were assessed 3–6 months following the surgery in both cases and controls. Depression was evaluated by using Beck Depression Inventory (BDI) questionnaire-II-Persian. Sexual function was assessed using the Female Sexual Function Index (FSFI). The average BDI in cases was 15.37 ± 7.6 and in controls was 13.06 ± 6.7. Mild to moderate depression was detected 57.3 percent of whom with hysterectomy and 36.5 percent of whom with C/S, the BDI sum score did not differ significantly between cases and controls ( p = .096). The FSFI in cases was 20.06 ± 6.96, and controls was 21.7 ± 9.83 without any significant difference ( p = .364). The depression had not been significantly different between women who underwent hysterectomy and were not following 3–6 months after surgery. Furthermore, both groups had impaired sexual function after the surgery.